Hubungan Harga dan Lokasi dengan Keputusan Pembelian Siomay Raos Bandung (Survei pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Slamet Riyadi Surakarta) - Kusuma, Alvito Chandra; Tyas, ⁠Nilam Nur; Astuti, Dwi Indri; Rahadhini, Marjam Desma (Innovative: Journal Of Social Science Research, 2025)
The culinary business competition in Surakarta City is getting tighter, especially in the snack segment such as siomay. Consumer purchasing decisions are not only influenced by taste, but also by price and location factors. Siomay Raos Bandung as a business actor in this sector needs to understand the extent to which these two factors influence students' purchasing decisions, especially at the Faculty of Economics, Slamet Riyadi University, Surakarta. This study uses a quantitative approach with a survey method. A sample of 30 respondents was selected purposively, namely active students who had purchased Siomay Raos Bandung at least once in the last three months. Data collection was carried out through a closed questionnaire with a Likert scale, and analyzed using multiple correlations to determine the relationship between price (X₁) and location (X₂) with purchasing decisions (Y). The results of the study showed that both price and location were significantly related to purchasing decisions, with location having a slightly more dominant influence. This finding provides an important impression for Siomay Raos Bandung's marketing strategy to better adjust prices to students' purchasing power and choose a strategic and easily accessible business location.